2003
DOI: 10.1179/joc.2003.15.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Concentrations of Cefepime in Experimental Necrotizing Pancreatitis

Abstract: To evaluate the penetration of cefepime in the inflamed pancreas, three doses of 50 mg/kg were administered intramuscularly at 8-h intervals after induction of acute necrotizing pancreatitis using intraperitoneal injection of DL-ethionine in 35 rabbits and in 33 controls. Animals were sacrificed and concentrations of cefepime were determined by a microbiological assay. Cefepime reached its peak concentrations 60 min after the last drug dose when mean values of 46.05 microg/ml, 22.34 microg/g and 34.74 microg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In two studies, after a single intravenous dose of ertapenem or imipenem, concentrations in pancreatic tissue and juice, respectively, were low but above the minimum inhibitory concentrations for the main pathogens responsible for intra-abdominal infections [22,43,44]. Several studies of animal models of acute pancreatitis [24][25][26] showed penetration within necrotic tissue to levels above the minimal inhibitory concentrations of common pathogens, and a single study [23] demonstrated good cefepime concentrations in pancreatic pseudocyst fluid or pancreatic resection specimens for cancer. However, pancreatic necrotic tissue during acute pancreatitis was not studied.…”
Section: P Valuementioning
confidence: 99%
See 1 more Smart Citation
“…In two studies, after a single intravenous dose of ertapenem or imipenem, concentrations in pancreatic tissue and juice, respectively, were low but above the minimum inhibitory concentrations for the main pathogens responsible for intra-abdominal infections [22,43,44]. Several studies of animal models of acute pancreatitis [24][25][26] showed penetration within necrotic tissue to levels above the minimal inhibitory concentrations of common pathogens, and a single study [23] demonstrated good cefepime concentrations in pancreatic pseudocyst fluid or pancreatic resection specimens for cancer. However, pancreatic necrotic tissue during acute pancreatitis was not studied.…”
Section: P Valuementioning
confidence: 99%
“…Furthermore, patients with IPN may require immediate antibiotic therapy for a co-existing infection at another site. The penetration of antibiotics within foci of pancreatic necrosis has been poorly evaluated but may be limited [18][19][20][21][22][23][24][25][26]. Thus, whether antibiotic exposure before the collection of pancreatic samples sterilizes the microbiological findings is unclear.…”
mentioning
confidence: 99%
“…59 Cefepime was also studied in animal models with simulated INP and peak cefepime concentrations between 22.34 and 75 mg/kg, and 6-hour levels were 11.75 mg/kg. 11,18,40 It appears that higher doses and longer infusion times may be necessary to achieve PK/PD targets for an MIC of 8 µg/mL.…”
Section: Cephalosporinsmentioning
confidence: 99%